a) \(10x^2-29x+10\)
\(=10x^2-4x-25x+10\)
\(=2x\left(5x-2\right)-5\left(5x-2\right)\)
\(=\left(5x-2\right)\left(2x-5\right)\)
\(\text{a) }10x^2-29x+10\\ =10x^2-25-4x+10\\ =5x\left(2x-5\right)-2\left(2x-5\right)\\ =\left(5x-2\right)\left(2x-5\right)\)
\(\text{b) }x^2-4xy+3y^2\\ =x^2-3xy-xy+3y^2\\ =x\left(x-3y\right)-y\left(x-3y\right)\\ =\left(x-y\right)\left(x-3y\right)\)
\(\text{c) }8-x^3=\left(2-x\right)\left(4+2x+x^2\right)\)
\(\text{d) }2x^2-11x+12\\ =2x^2-8x-3x+12\\ =2x\left(x-4\right)-3\left(x-4\right)\\ =\left(2x-3\right)\left(x-4\right)\)
\(\text{e) }-2x^2+5x-3\\ =-2x^2+2x+3x-3\\ =\left(2x-2x^2\right)-\left(3-3x\right)\\ =2x\left(1-x\right)-3\left(1-x\right)\\ =\left(2x-3\right)\left(1-x\right)\)
\(\text{f) }x^2-9x+20\\ =x^2-4x-5x+20\\ =x\left(x-4\right)-5\left(x-4\right)\\ =\left(x-5\right)\left(x-4\right)\)
\(\text{h) }2a^2-7a+3\\ =2a^2-a-6a+3\\ =a\left(2a-1\right)-3\left(2a-1\right)\\ =\left(a-3\right)\left(2a-1\right)\)
\(\text{i) }a^2-a-6\\ =a^2-3a+2a-6\\ =a\left(a-3\right)+2\left(a-3\right)\\ =\left(a+2\right)\left(a-3\right)\)\(\text{k) }x^2+x-12\\ =x^2+4x-3x-12\\ =x\left(x+4\right)-3\left(x+4\right)\\ =\left(x-3\right)\left(x+4\right)\)\(\text{ m) }3\left(x+1\right)^2-4x^2-4x\\ =3\left(x+1\right)^2-\left(4x^2+4x\right)\\ =3\left(x+1\right)^2-4x\left(x+1\right)\\ =\left(3x+3-4x\right)\left(x+1\right)\\ =\left(3-x\right)\left(x+1\right)\) \(\text{n) }3x\left(1-2x\right)-10x+5\\ =3x\left(1-2x\right)+\left(5-10x\right)\\ =3x\left(1-2x\right)+5\left(1-2x\right)\\ =\left(3x+5\right)\left(1-2x\right)\)
\(\text{o) }x^2+xy-xz-yz\\ =x\left(x+y\right)-z\left(x+y\right)\\ =\left(x-z\right)\left(x+y\right)\)